The Initial and Potential Impact of Preferential Access to the U.S. Market under the African Growth and Opportunity Act - Brenton, Paul (World Bank, Washington, D.C., 2013)
The ability to export clothing products under preferences with liberal rules of origin is the key factor currently determining whether the African Growth and Opportunity Act (AGOA) has a significant impact on non-oil exporting African countries. At present only a small number of countries receive substantial benefits and least developed countries that do not receive preferences for clothing have yet to see an impact of AGOA on their overall exports. However, the benefits from exporting clothing under AGOA appear fragile in the face of the removal of quotas in the United States on major suppliers, such as China, at the end of 2004, and the planned removal of the liberal rules of origin that allow for the global sourcing of fabrics from least-cost locations. To entrench and enhance the benefits of AGOA, it is important that the scheme be extended over a much longer period, if not made permanent, and the special liberal rules of origin for clothing products be extended considerably beyond 2004. The effective inclusion of textile products and a number of high-duty agricultural products would also help to broaden the range of opportunities for African exporters in the U.S. market. Nevertheless it is important that the opportunities created by AGOA are integrated into a broader framework for promoting trade and that it be recognized that if the opportunities offered by more open trade are to be exploited, there must be concerted efforts to improve the environment for investment countries covered by AGOA.